2008
DOI: 10.4136/ambi-agua.49
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Bioaccumulation in the Brazilian Amazonian Tucunares (Cichla sp., Cichlidae, Perciformes)

Abstract: There are emissions of mercury to the atmosphere, soil and rivers of the Brazilian Amazon stem from many sources. Once in the atmosphere, the metal is oxidized and immediately deposited. In the water, the transformation to methylmercury takes place mostly by the action of microorganisms. The formation of methylmercury increases the dispersion and bioavailability of the element in the aquatic environment. Methylmercury can be assimilated by plankton and enters the food chain. The concentration of mercury increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
0
0
2
Order By: Relevance
“…In the present study, C. monoculus showed high concentrations of Hg, and a positive relationship between this metal and its weight and length. Similar observations were reported for this species by Vera et al (2008) in the Tapajós river and by Bastos et al (2008) in the Madeira River. Soares et al (2016) also found a positive relationship between Hg and standard length (but not weight) for Cichla temensis in the Negro river.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, C. monoculus showed high concentrations of Hg, and a positive relationship between this metal and its weight and length. Similar observations were reported for this species by Vera et al (2008) in the Tapajós river and by Bastos et al (2008) in the Madeira River. Soares et al (2016) also found a positive relationship between Hg and standard length (but not weight) for Cichla temensis in the Negro river.…”
Section: Discussionsupporting
confidence: 91%
“…Os esforços aqui realizados, tem o intuito de oferecer aos laboratórios nacionais paticulares e/ou governamentais, envolvidos com a atividade pesqueira, um programa de proficiência de baixo custo e fácil adesão, que atenda aos requisitos de acreditação baseados na norma ABNT NBR ISO/IEC 17025 (2005), e deste modo, trazer uma contribuição para a cadeia produtiva do pescado. (Donatti, 2011;BAM, 2010).…”
Section: Relevânciaunclassified
“…A especie escolhida destaca-se na exportação de pescado e os individuos adquiridos apresentaram baixos teores de As, Cd, Pb e teores Hg dentro dos limites estipulados pela Anvisa, legislação europeia e Codex stan (Lima, 2005;Ysrael, 2008;Kering, 2009). …”
Section: Propriedades De Interesse Para Os Mensurandos Hg As CD E Pbunclassified